2019
DOI: 10.1186/s40545-019-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of infertility in Ghana: retrospective study at the cape coast teaching hospital

Abstract: BackgroundInfertility is a major challenge for couples globally. Due to low income levels and the high cost of other assisted reproductive techniques, pharmacotherapy remain the major first line treatment option for infertility in Sub-Saharan Africa.ObjectiveThe aim of this study was to assess the prevalence of infertility as well as the effectiveness and success achieved following infertility pharmacotherapy at the Cape Coast Teaching Hospital in Ghana.MethodsThis study was a retrospective observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Among the healthcare professionals interviewed were doctors and nurses from the four fertility centers who provided direct care to the patients. The respondents expressed diverse views on the factors that influenced discontinuation of infertility treatment in Ghana, which were not discovered in our previous study since it relied on secondary data [ 16 ]. It is evident from this qualitative study that patients who discontinued treatment cited various reasons to back their actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the healthcare professionals interviewed were doctors and nurses from the four fertility centers who provided direct care to the patients. The respondents expressed diverse views on the factors that influenced discontinuation of infertility treatment in Ghana, which were not discovered in our previous study since it relied on secondary data [ 16 ]. It is evident from this qualitative study that patients who discontinued treatment cited various reasons to back their actions.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly due to the fact that most fertility experts/researchers in the sub-region are concerned with positive treatment outcomes, and tend to ignore clients who may decide to stop treatment. Our previous study which assessed the outcome of pharmacotherapy among infertile couples revealed that approximately 19.4% of them conceived after going through drug treatment [ 16 ]. However, the retrospective nature of that study made it impossible to assess how clients complied with treatment and the reasons for non-compliance, particularly in the patients who had unsuccessful treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the source of information regarding ART's availability to clients had a significant effect on their choice to employ ART services. Electronic (Internet, TV, and radio) and print (magazines and newspapers) sources of information regarding the availability of ART services in Ghana are available, as are satisfied clients, friends, and members of social networks [ 8 , 19 , 20 ]. Also, in another study, it is reported that the helpful sources of information for infertility are written health center information on childlessness and the subsequent discussion with fertility clinic staff.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, about 10–15% of reproductive-age females are unable to naturally get pregnant within a year of unguarded sexual intercourse [ 8 ], and the phenomenon of infertility effect is between 60 and 168 million people worldwide [ 4 ], accounting for about 13 to 15% of couples [ 9 ]. Also, a study reported that infertility accounts for about one-third of the population in the sub-Saharan African region [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, the estimated prevalence of infertility ranges from 12 to 17% (Arhin et al, 2019; Fledderjohann & Johnson, 2016; Geelhoed et al, 2002; Larsen, 2000) with male factor infertility and tubal damage reported as the most common causes (Fiander, 1990). However, data are limited, with no national-level estimates based on a clinical definition of infertility (i.e., the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse or due to an impairment of a person’s capacity to reproduce) (Zegers-Hochschild et al, 2017), which is a more informative measure for estimating the potential need for clinical care.…”
mentioning
confidence: 99%